1991
DOI: 10.1177/074873049100600107
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Inputs Influence the Performance of a Spiking, Movement-Sensitive Neuron in the Visual System of the Blowfly

Abstract: Long-term extracellular recordings from a spiking, movement-sensitive giant neuron (H1) in the third optic ganglion of the blowfly Calliphora vicina (L.) revealed periodic endogenous sensitivity fluctuations. The sensitivity changes showed properties typical of an endogenous circadian rhythm. This was true for the responses in reaction to intensity changes of visual patterns as well as for the responses elicited by pattern movement. For these two types of stimuli, the circadian fluctuations were comparable, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The sensitivity of locust photoreceptors follows a diurnal rhythm as a result of changes in photoreceptor membrane properties (Cuttle et al, 1995) and the extent of rhabdom turnover (Williams, 1983). Circadian changes under constant dark conditions have also been recorded in the optic neuropiles of insects, in the lamina and lobula plate of flies (Pyza and Meinertzhagen, 1993;Bult et al, 1991) and in the lobula complex of cockroaches (Bult and Mastebroek, 1993) and bees (Kaiser and SteinerKaiser, 1983). The circadian rhythmicity we have demonstrated in DCMD spiking activity could therefore arise from changes in LGMD and/or DCMD, or from changes in neurones presynaptic to them.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of locust photoreceptors follows a diurnal rhythm as a result of changes in photoreceptor membrane properties (Cuttle et al, 1995) and the extent of rhabdom turnover (Williams, 1983). Circadian changes under constant dark conditions have also been recorded in the optic neuropiles of insects, in the lamina and lobula plate of flies (Pyza and Meinertzhagen, 1993;Bult et al, 1991) and in the lobula complex of cockroaches (Bult and Mastebroek, 1993) and bees (Kaiser and SteinerKaiser, 1983). The circadian rhythmicity we have demonstrated in DCMD spiking activity could therefore arise from changes in LGMD and/or DCMD, or from changes in neurones presynaptic to them.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the response amplitude during dusk might have been affected by circadian rhythms that modulate the sensitivity of the H1-neuron. It has been shown that both the spontaneous activity of the H1neuron and its sensitivity to image motion decrease in the evening (Bult, Schuling, & Mastebroek, 1991). However, apart from experiments at very low light levels which were always performed in the evening (because only then was it warm enough; early in the morning it was always cooler than 17掳C), the data were pooled from experiments done in the morning and in the afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…If the recorded neurons do play a role in the circadian system, stronger and perhaps even antagonistic responses to light might, therefore, be expected in the early and late night. Striking circadian differences in responsiveness have, indeed, been observed in visual interneurons in a fly, a cockroach, and a bee (Kaiser, 1983;Bult et al, 1991;Bult and Mastebroek, 1993), and suggest that those neurons are under circadian control. To distinguish between neurons that merely re- ceive efferent input from a clock and intrinsic elements of the circadian system, one would have to stimulate the recorded neurons electrically and monitor their phaseshifting effects on the circadian output.…”
Section: Principal Neurons Of the Amementioning
confidence: 94%